The Effect of Information Technology Mastery ond Work Discipline on Employee Performance Through Work Productivity as an Intervening Variable at PT. Incasi Raya - Lorenz Kintana Luwiensky; John Veri (Jurnal Multidisiplin Sahombu, 2025)
This study aims to examine the influence of information technology mastery and work discipline on employee performance through work productivity as an intervening variable at PT. Incasi Raya. Data collection methods were conducted through surveys and questionnaires, with a sample of 67 respondents. The analysis method used was structural equation modeling using SmartPLS. The results of the study showed a significant influencemastery of information technology to work productivity. There is a significant influence work discipline to work productivity. There is a significant influence mastery of information technology to employee performance. There is a significant influence work discipline to employee performance. There is a significant influence work productivity to employee performance. Work productivity mediates the influence of mastery of information technology to employee performance.Work productivity mediates the influence of work discipline to employee performance